ORGANIZATION OF MANAGEMENT AND PROVISION OF RESOURCES OF FORCES AND MEANS OF CIVIL PROTECTION DURING EMERGENCY RESCUE AND OTHER URGENT WORK - Ziyodullayev I; Ziyodullayeva R; Shamansurov S.; Naimova M (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the issues of ensuring the functioning and increasing the efficiency of the system of material and technical support of civil protection measures in a market economy by applying a logistic approach to preventing, mitigating the influence of potentially dangerous factors and eliminating emergency situations.